Determination of Genetic Mutation Profile of drpr Gene in Drosophila melanogaster using High-Resolution Melting Analysis - Rudi Arfiansyah; Tri Puspita Roska; Herlina Rante; Firzan Nainu; Ahmad Mu'arif (Biota, 2022)
Genotype determination of experimental animals is generally conducted using sequencing methods that require expensive cost as well as experience and special equipment. This study aimed to determine the presence of drpr gene mutation in Drosophila melanogaster using coupled real time PCR-High Resolution Melting (real time PCR-HRM) as an alternative method. Two types of fly samples, w1118 and drprΔ5 were used as wildtype control and mutant genotype, respectively. The DNA from twenty of each w1118 and mutant drprΔ5 flies were isolated and amplified using real time PCR. The generated amplicons were then further processed by HRM method at the temperature of 60-95°C. This study demonstrated that the real time PCR-HRM method could distinguish wildtype control w1118 and mutant drprΔ5 based on the HRM data with the confidence level was more than 90%. Therefore, this study provides an evidence that real time PCR-HRM method might be beneficial to screen the mutant genotype from its wildtype counterpart based on differences in the melting temperatures due to changes at nucleotide base level